2003
DOI: 10.1073/pnas.0635075100
|View full text |Cite
|
Sign up to set email alerts
|

Context sensitivity of activity-dependent increases in cerebral blood flow

Abstract: Functional neuroimaging in humans is used widely to study brain function in relation to human disease and cognition. The neural basis of neuroimaging signals is probably synaptic activity, but the effect of context, defined as the interaction between synaptic inhibition, excitation, and the electroresponsive properties of the targeted neurons, is not well understood. We examined here the effect of interaction of synaptic excitation and net inhibition on the relationship between electrical activity and vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…The activation seen in functional imaging studies probably results from excitation rather than inhibition (Waldvogel et al 2000), while EEG reflects a competitive balance between them. Some authors, though, have asserted that neuronal inhibitions can raise fMRI and PET measures under certain extreme conditions (Tagamets & Horwitz 2001;Caesar et al 2003). In this issue, Horwitz et al (2005) evaluated the effect on PET and fMRI of using a large-scale excitatory and inhibitory computational model applied to a delayed matched-tosample task.…”
Section: Discussionmentioning
confidence: 99%
“…The activation seen in functional imaging studies probably results from excitation rather than inhibition (Waldvogel et al 2000), while EEG reflects a competitive balance between them. Some authors, though, have asserted that neuronal inhibitions can raise fMRI and PET measures under certain extreme conditions (Tagamets & Horwitz 2001;Caesar et al 2003). In this issue, Horwitz et al (2005) evaluated the effect on PET and fMRI of using a large-scale excitatory and inhibitory computational model applied to a delayed matched-tosample task.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we considered the same rule for both EPSPs and IPSPs to calculate the synaptic activity. This assumption was based on experimental studies (Caesar et al 2003). Finally, we concluded that the synaptic activity was linearly related to N(t) (see Eqs.…”
Section: Discussionmentioning
confidence: 85%
“…The effect of afferent neuronal context has recently been supported by electrophysiological experiments in the rat cerebellum (Caesar et al, 2003), where it was shown that simultaneously converging excitatory and inhibitory inputs to a region result in a smaller change in local blood flow than would be expected if they were purely additive. Our own modeling results also suggest that how such simultaneous inputs are reflected in regional metabolsim depends on the amount of local excitatory recurrence in the region .…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, methods such as structural equation modeling (SEM (McIntosh & Gonzalez-Lima, 1992;McIntosh & Gonzalez-Lima, 1994) and dynamic causal modeling (DCM; do not take synaptic inhibition and energetic consequences of modulatory neurotransmitter effects into account. For example, how synaptic inhibition affects local blood flow (fMRI signal) is not well understood (Jueptner & Weiller, 1995;Magistretti & Pellerin, 1999;Logothetis et al, 2001;Caesar et al, 2003). Because of this, a positive connection weight can not necessarily be interpreted as an excitatory underlying connection.…”
Section: Introductionmentioning
confidence: 99%